Molecular modelling of the gastric barrier response, from infection to carcinogenesis - Traulsen, J; Zagami, C; Daddi, AA; Boccellato, F (Elsevier, 2021)
The lining of the stomach is a tight monolayer of epithelial cells performing functions in digestion and a protective barrier against gastric acid, toxic metabolites and infectious agents, including Helicobacter pylori. The response of the epithelial barrier to infections underlies gastric pathologies, including gastric cancer. H. pylori has the unique capacity to colonise the gastric mucosa while evading the immune system. The colonised mucosa initiates an inflammatory response to fight the infection and a strong regenerative program to avoid barrier failure and ulceration. This response changes the morphology and cell composition of the gastric epithelium and in parallel it might contribute to the accumulation of somatic mutations leading to cellular transformation. Genetically modified mice, cell lines and human-derived organoids are the main biological models to study the gastric epithelial barrier. With these models it is possible to dissect the stepwise process of tissue adaptation to infection that places the epithelium at risk of malignant transformation.